Activation of a Helper and Not Regulatory Human CD4+ T Cell Response by Oncolytic H-1 Parvovirus - Moralès, Olivier; Richard, Audrey; Martin, Nathalie; Mrizak, Dhafer; Sénéchal, Magalie; Miroux, Céline; Pancré, Véronique; Rommelaere, Jean; Caillet-Fauquet, Perrine; de Launoit, Yvan; Delhem, Nadira (PLOS ONE, 2012)
Background H-1 parvovirus (H-1 PV), a rodent autonomous oncolytic parvovirus, has emerged as a novel class of promising anticancer agents, because of its ability to selectively find and destroy malignant cells. However, to probe H-1 PV multimodal antitumor potential one of the major prerequisites is to decipher H-1 PV direct interplay with human immune system, and so prevent any risk of impairment. Methodology/Principal findings Non activated peripheral blood mononuclear cells (PBMCs) are not sensitive to H-1 PV cytotoxic effect. However, the virus impairs both activated PBMC proliferation ability and viability. This effect is related to H-1 PV infection as evidenced by Western blotting detection of H-1 PV main protein NS1. However, TCID50 experiments did not allow newly generated virions to be detected. Moreover, flow cytometry has shown that H-1 PV preferentially targets B lymphocytes. Despite seeming harmful at first sight, H-1 PV seems to affect very few NK cells and CD8+ T lymphocytes and, above all, clearly does not affect human neutrophils and one of the major CD4+ T lymphocyte subpopulation. Very interestingly, flow cytometry analysis and ELISA assays proved that it even activates human CD4+ T cells by increasing activation marker expression (CD69 and CD30) and both effective Th1 and Th2 cytokine secretion (IL-2, IFN-γ and IL-4). In addition, H-1 PV action does not come with any sign of immunosuppressive side effect. Finally, we have shown the efficiency of H-1 PV on xenotransplanted human nasopharyngeal carcinoma, in a SCID mouse model reconstituted with human PBMC. Conclusions/Significance Our results show for the first time that a wild-type oncolytic virus impairs some immune cell subpopulations while directly activating a Helper CD4+ T cell response. Thus, our data open numerous gripping perspectives of investigation and strongly argue for the use of H-1 PV as an anticancer treatment.